Strain rock energy approach to the optimisation of rock drilling processes - Munoz, H.E.; Taheri, A.; Chanda, E.; Xu, C.; Grant, D.; Franca, L. (Deep Mining 2014: Proceedings of the Seventh International Conference on Deep and High Stress Mining, 2014)
To study the effects of strain energy characteristics of intact rock on drilling performance, a series of uniaxial compressive tests with a single-cyclic loading on three granite rock samples were performed. Additionally, a number of rotary drilling tests using a small scale rig having an impregnated diamond core bit under the kinematically controlled steady-state response were carried out to measure the energy expended during drilling. It was found that the relation of weight and torque on the bit to the depth of cut on the granite samples can be described by three successive linear regimes governing the bit-rock interaction. Results from cutting tests by using laboratory-prepared impregnated diamond leached segments were further analysed to determine the intrinsic specific energy for rock cutting, i.e. the energy strictly consumed in pure cutting action. Finally, a non-linear relationship between the strain energy and the intrinsic specific energy was proposed.